KAJIAN TEKNIS PRAKTEK UJI COBA SISTEM TEBANG JALUR DAN TANAM INDONESIA - Djaban Tinambunan; Sri Sutopo (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
The investigation of three concessionaires in Kalimantan practicing the trial of Indonesian Strip Cutting and Planting System was conducted in 1994. All the companies are in the early stage of the trial and, therefore, the focus of investigation is limited to trial preparation and timber harvesting with the aim of describing the real practices and various problems faced in the field.It is found that the productivity of each activity in preparation and timber harvesting in the Indonesian Strip Curing and Planting System (A) is lower than those in the Indonesian Selective Cutting and Planting System (B). The comparison of several productivities are as follows : (I) Felling: 47 cu. m/day forA and 85 cu. m/day for B: (2) Skidding : 37 cu.m/day for A and 85 cu.m/day for B; (3) Loading-unloading : 55 cu.m/day for A and 150 cu.m/day for B; (4) Hauling :. 50 cu.m/trip forA and 64 cu.m/trip for B. The above figures and observation in the field lead to the notion of several problems faced such as : (1) in matching the required strip direction and real field condition ; (3) improper skill of workers; (4) unsuitable wage system; (5) inability to utilize the small diameter logs; (6) too large cable used for skidding; (7) too large log clamp available on loader tractor: (8) difficulty in handling small diameter logs onto logging truck; and (9) high percentage of land area disturbed due to large equipment and strip width limitation.The trial is still in the early stage and the information is very limited and therefore, further investigations is strongly recommended to cover more locations and aspects so that the final results can be used by the authority to make sound conclusions in selecting the final arrangement of the Indonesian Strip Cutting and Planting System.